2019
DOI: 10.1002/cctc.201900999
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic Disproportionation of Formic Acid to Methanol by an Iridium Complex Immobilized on Bipyridine‐Periodic Mesoporous Organosilica

Abstract: We report the first example of using heterogeneous Iridium (Ir) catalysts under atmospheric pressure conditions to achieve the catalytic disproportionation of formic acid to methanol. IrCp* complex (Cp* = pentamethylcyclopentadienyl (� 5 -C 5 Me 5 )) was immobilized on the pore surface of the periodic mesoporous organosilica synthesized from a precursor mixture of ethane (Et) and 2,2'-bipyridine (BPy)-bridged organosilanes (Ir-Et-BPy-PMO). Ir-Et-BPy-PMO showed unique catalysis with higher selectivity of methan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 34 publications
1
13
0
Order By: Relevance
“…When the PMO‐based material 1 and the homogeneous catalyst 3 , having an electron withdrawing CF 3 group, were applied, the amount of FA slowly decreased over time while the yield of MeOH increased. The use of 1 generated 87 μmol MeOH after 96 h. As noted in a previous report, the increased MeOH yield obtained with 1 cannot be explained solely by the electronic effect of substituents on the BPy ligands. Thus, a kinetics study was performed based on the above time course measurements.…”
Section: Kinetics Analysissupporting
confidence: 60%
See 2 more Smart Citations
“…When the PMO‐based material 1 and the homogeneous catalyst 3 , having an electron withdrawing CF 3 group, were applied, the amount of FA slowly decreased over time while the yield of MeOH increased. The use of 1 generated 87 μmol MeOH after 96 h. As noted in a previous report, the increased MeOH yield obtained with 1 cannot be explained solely by the electronic effect of substituents on the BPy ligands. Thus, a kinetics study was performed based on the above time course measurements.…”
Section: Kinetics Analysissupporting
confidence: 60%
“…Here, A is the cross sectional area of the PMO pores [m 2 ], S BET is the specific surface area with a value of 802 m 2 g −1 , w is the mass of catalyst used with a value of 0.286 g, S sa is the cross‐sectional pore area calculated as π( d DFT /2)×2 [m 2 ] and S area is the surface area per pore, calculated as 2π( d DFT /2)×2 dx [m 2 ]. A standard pore length, L , of 3.2 μm was used on the basis of scanning electron microscopy (SEM) observations, and so the average diffusion distance of H 2 was found to be 1.6 μm. The experimental results were substituted into Eq.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The analogous heterogeneous catalyst Ir17a was found to be more selective (up to 8.3%) for methanol production in comparison to the homogeneous Ir-bipyridine catalysts (1.4–4.3%). 401 Neary and Parkin reported that the molybdenum complex Cp R Mo(PMe 3 ) 3– x (CO) x H afforded 21% selectivity of MeOH and methyl formate formation in benzene at 100 °C. 402 In 2016, the Cantat group also reported a metal-free system for the formic acid disproportionation reaction using stoichiometric quantities of dialkylborane reagents ( B01 ), where boroformate and borohydride intermediates were formed via the decarboxylation of formate and followed by undergoing disproportionation of formates to formaldehyde and methanol.…”
Section: Methanol Economymentioning
confidence: 99%
“…In addition, chemical hydrogen storage is also an environmentally important research topic. Several types of iridium-catalyzed hydrogen storage reactions are known in the literature [28][29][30][31][32][33][34][35][36][37][38][39][40], however, only a few heterogeneously catalyzed, iridium-based hydrogen storage systems have been described recently [41][42][43].…”
Section: Introductionmentioning
confidence: 99%